Historja i literatura zydowska : ze szczegolnem uwzglednieniem historji Zydow w Polsce : dla klas wyzszych szkol srednich - Balaban, Majer, 1877-1943. (Warszawa : Wydawnictwa Artystyczne i Filmowe, 1982)
A history of the Jews from ancient times to 1795, with special emphasis on the history of the Jews in Poland. A text for high school students.
t. 1. Od najdawniejszych czasow do upadku swiata starozytnego -- t. 2. Od upadku swiata starozytnego do konca wiekow srednich -- t. 3. Od wygnania Zydow z Hiszpanji do rewolucji francuskiej.
Reprint (Vol. 1). Originally published: 3rd ed. Lwow : Nakl. Zakladu Nar. im. Ossolinskich.
Reprint (Vol. 2). Originally published: 2nd ed. Lwow : Nakl. Zakladu Nar. im. Ossolinskich.
Reprint (Vol. 3). Originally published: Lwow : Nakl. Zakladu Nar. im. Ossolinskich, 1925.
Keywords: Jews -- History; Jewish literature -- History and criticism; Jews -- Poland